Improving educational outcomes: Analyses of intervention and public opinion; Verbesserung von Bildungsergebnissen: Analysen von Interventionen und öffentlicher Meinung - Katharina Wedel (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2024)
Katharina Wedel prepared this study while she was working at the Center for the Economics of Education at the ifo Institute. The study was completed in September 2023 and accepted as doctoral thesis by the Department of Economics at LMU Munich. It consists of four distinct empirical essays that address various aspects of the economics of education. Chapter 2 sheds light on the interaction of two inputs into the education production function: instruction time and teacher qualifications. The results show that teacher qualifications play a moderating role for the effect of instruction time on student achievement. Chapter 3 examines dropout from a mentoring program designed to help disadvantaged adolescents and analyzes a program agency's cost-benefit trade-offs in the decision to target additional interventions to prevent dropout. Chapter 4 investigates public opinion towards targeted financial support and the role of external circumstances compared to own effort for (educational) success. This chapter shows how information on the differences in academic-track attendance by parental background in Germany increases the perception that external circumstances determine educational success, and private donations to charities but does not affect demand for redistributive education spending. Finally, chapter 5 studies the consequences of technological change on individuals' labor-market expectations and their intentions to participate in further training. Experimental results show that information about the automatability of one's occupation affects labor-market expectations and increases the likelihood to participate in further training and retraining. – – Die Dissertation besteht aus vier eigenständigen empirischen Aufsätzen, die sich mit verschiedenen Aspekten der Bildungsökonomie befassen. Kapitel 2 beleuchtet die Interaktion von zwei Inputs der Bildungsproduktionsfunktion: Unterrichtszeit und Lehrerqualifikationen. Die Ergebnisse zeigen, dass sich mehr Unterrichtszeit positiv auf Schülerleistungen auswirkt, wobei dieser Effekt deutlich größer ist, wenn Kinder von besser qualifizierten Lehrkräften unterrichtet werden. Kapitel 3 untersucht den Abbruch von Mentoringbeziehungen. Es analysiert die Kosten-Nutzen-Abwägungen einer Programmagentur bei der Entscheidung, zusätzliche Maßnahmen zur Verhinderung des Abbruchs zu ergreifen. Kapitel 4 untersucht die öffentliche Meinung zu gezielter finanzieller Unterstützung und die Rolle äußerer Umstände im Vergleich zu eigener Anstrengung für (Bildungs-)Erfolg. Dieses Kapitel zeigt, wie Information über die Unterschiede in den Raten des Gymnasialbesuchs nach elterlichem Hintergrund in Deutschland die Wahrnehmung, dass äußere Umstände den Bildungserfolg beeinflussen, sowie die private Spendenbereitschaft an Wohltätigkeitsorganisationen erhöhen, nicht aber die Nachfrage nach umverteilenden Bildungsausgaben. In Kapitel 5 werden die Auswirkungen des technologischen Wandels auf Arbeitsmarkterwartungen und Weiterbildungsabsichten von Individuen untersucht. Die experimentellen Ergebnisse zeigen, dass Information über die Automatisierbarkeit des eigenen Berufs die Arbeitsmarkterwartungen beeinflusst und die Wahrscheinlichkeit einer Teilnahme an Weiterbildungen und Umschulungen erhöht.
Keywords: C21; C53; D04; D63; D64; D83; H11; H52; I21; I24; I25; I29; J24; O33; 330; Education Production Function; Instruction Time; Student Achievement; Teacher Qualifications; Program Dropout; Prediction; Machine Learning; Information; Survey Experiment; Charitable Donations; Policy Preferences; Automation; Further Training; Labor-Market Expectations